Novel self-healing concrete for roof repair - Aw, Zhi Wei (Nanyang Technological University, 2022)
This project serves to explore the use and optimization of self-healing bacteria capsules into screed mix to solve the leaking issues in HDB. Spore forming bacteria – Bacillus was chosen as the self-healing agent to be added into screed to analyse the effect to the self-healing for naturally formed minor cracks which is very commonly seen in screed due to shrinkage. Bacteria will first be encapsulated with nutrients before adding into screed mix. During the first phase of study, bacteria dosage was adjusted to 20% of the previous FYP design mix used in pure cement case because cement only formed 20% of screed powder. The bacteria added screed has delivered better crack closure and also water permeability results. Cracks healed better than control sample with less water to pass though the sample. The compressive strength of bacteria added screed also slightly higher than control sample. The optimisation of bacteria capsules was then considered in second phase of study after bacteria capsules has shown healing ability to screed mix. It served as an important strategy with purpose to determine the most economical mix design to drive higher profit margin without affecting the performance at the same time. In overall, the results suggested that the use of bacteria capsules in screed is highly recommended. Nonetheless, additional studies and investigations would be required to produce a comprehensive reference guide for optimizing the combination.